The relationship between the use of social networking sites, perceived social support and spirituality on loneliness among university students in Klang Valley, Malaysia - Mohamed, Nur Nadhira Izzati; Marof, Aini Azeqa; Sulaiman, Abdul Hadi (Human Resource Management Academic Research Society, 2023)
Loneliness is a prevalent concern among university students that prompts substantial scholarly attention. This study examines the complex relationship between social networking site usage, perceived social support, spirituality, and loneliness among undergraduates in the Klang Valley, Malaysia. Data from 303 participants from three Malaysian public universities in Klang Valley were gathered using self-administered questionnaires. Measurement tools included the Facebook Intensity Scale (FBI) for social networking, the Multidimensional Scale of Perceived Social Support (MSPSS), the Daily Spiritual Experience Scale (DSES), and the UCLA Loneliness Scale (ULS-8). Findings indicated a substantial portion of respondents reporting high social networking site usage and perceived social support, while a significant portion reported lower spirituality and loneliness. Gender-based demographic analysis revealed male undergraduates experiencing less loneliness compared to their female counterparts, though no significant differences emerged in social networking site usage, perceived social support, or spirituality. Correlation analyses revealed no significant relations between loneliness and social networking site usage or spirituality. However, perceived social support showed a notable negative correlation with loneliness. Multiple regression analysis identified perceived social support as the exclusive predictor of undergraduate students' loneliness. In conclusion, this study explores the interplay of social networking site usage, perceived social support, spirituality, and loneliness among Klang Valley undergraduate students. It highlights that while social networking site usage and spirituality may not directly contribute to loneliness, perceived social support significantly mitigates loneliness. These findings have implications for interventions and support strategies to enhance the well-being of university students dealing with loneliness.